"Out of Sight and Out of Mind": Detachment and Men's Consumption of Male Sexual Dominance and Female Submission in Pornography. (December 2015) - Antevska, Aleksandra; Gavey, Nicola
It is generally accepted that pornography is widely consumed by young men and that mainstream heterosexual pornography is characterized by a dynamic of male sexual dominance and female submission. What is less agreed upon is whether such pornography is a source of "sexist education" (Flood 2010) for men or whether men engage with it in an empathic and ethical manner. In this study, we discuss findings from interviews with twenty-one young men about pornography and its consumption. They described it as normative for men to watch pornography and they described "extreme" content as "normal." It was clear that they were unused to having to account for the appeal of pornography. Men's discussion of male sexual dominance and female submission, and violence against women, within pornography was characterized by detachment. Most of the men did not take up the challenge to notice and critically respond to the sexism within the material they described. There were some exceptions, with a minority of the participants reflecting on the ethical dilemmas posed by their consumption of such pornography.